Literature, history and memory: the decline of the heroes in Castillos de fuego, by Ignacio Martínez de Pisón (XXI Century. Spanish Literature and Culture, 2024)
The present work analyses contemporary Spanish historical fiction through the novel Castillos de fuego (2023) by Ignacio Martínez de Pisón. It studies the dialectic between literature, history, and memory, and this choral novel can also be classified as 'literature of memory,' as it brings together a diverse array of characters that reflect the Spanish reality of the post-war period and early Francoism. Moreover, it illustrates a decline of heroes that allows for its analysis within the context of postmodernity. In conclusion, we find in it a novel that seeks to reconstruct the intrahistory of the national past through the demystification of both the period and its protagonists.
Keywords: historical novel; memory; Ignacio Martínez de Pisón; Spanish Civil War and postwar; decline of the hero